PRO-KONTRA WACANA PELEGALAN POLIGAMI DALAM ATURAN DAERAH (QANUN) DITANAH RENCONG ACEH - Husaidi husaidi; Sulfia Andika; Cindy Trisdiani; Khairul Hasan; Desi Maulida (SOURCE : Jurnal Ilmu Komunikasi, 2020)
The discourse on the legalization of polygamy that the Aceh Government wishes to set forth in the Family Qanun has become one of the issues that has spread among the community so that it has drawn pros and cons and products. As a special autonomous region that has the authority to carry out Islamic syari'at, of course this is relevant if it is stated in a Qanun, but people's perceptions certainly cannot be ignored. This research was conducted using qualitative methods with secondary data analysis techniques such as literature studies and using the Narative Review scheme. The results showed that although Aceh is an area that practices Islamic Syari’at, if it is in accordance with its wishes regarding domestic life (polygamy) it is not automatically accepted so that the pros and cons cannot be avoided. However, the fact that the practice of polygamy must be regulated in the legal system is important given the many cases of betel marriage which of course are regulated and emphasized the terms and sanctions that polygamy practice will pass.